Business Strategy for Future Car Rental Business in Road Transportation Industry with Scenario Planning - Adhika Aryamurti; Yos Sunitiyoso (CV. Publikasi Indonesia, 2025)
The road transportation in Jakarta experiencing significant growth due to the the increasing demand for transportation services that offer flexibility and convenience to provide solutions for customers, particularly for people with business purpose and tourist who have high mobility in Jakarta. This research focuses in identifying scenarios that may occur in car rental companies and aims to develop a business strategy for next 5 years in the car rental business as part of road transportation industry. Therefore, the author will evaluate the appropriate scenario planning in determining the business strategy for future car rental company by exploring the internal company and external environment using PESTEL and Porter’s Five Forces. Then, scenario planning analysis will be conducted where the driving forces will be identified through in-depth interview with regulators, experts, consumers, and person in industry players as stakeholders in the road transportation industry in Jakarta. Government Regulation and Customer Behaviour are the key uncertainties identified in this research which resulted four scenarios, which are Harmonized Growth, Opportunities Expansion, Reluctant Adoption, and Stalled Progress. Implications and Options will be created from each scenario presented.